CODE-SWITCHING ANALYSIS IN THE NOVEL A VERY YUPPY WEDDING - Aswarini Sentana (Jurnal Ilmiah Multidisiplin, 2022)
This is sociolinguistic research that analyzes code-switching occurrences in the Indonesian novel entitled A Very Yuppy Wedding. The aims of this research are to discover the types of code-switching and the factors that influence code-switching in the studied novel. The researcher in conducting this research used a descriptive qualitative method which is done through library research. The results of this research show that the types of code-switching in the conversation contained in the novel are intasentential switching, inter-sentential switching, and emblematic switching. Meanwhile, the factors that influence code-switching in the novel conversation are participant roles and relationships, situational factors, message intrinsic factors, and language attitudes, dominance, and security. This research found that inter-sentential switching dominates the types of code-switching in the novel. The characters often switch their language mostly because of language attitude, dominance, and security. It means that code-switching is viewed positively so that people tend to code-switch in their daily communication, and the switching is smooth.